Estudio de Impacto ambiental de la planta procesadora avícola "Frank" ubicada en el Cantón Loja, provincia de Loja - Zaragocín Sánchez, Bryan Israel (2019)
The objective of this research was the environmental impact study of the "Frank" Poultry Processing Plant, which allowed to evaluate the environmental impacts generated, through the use of an important matrix, in the different processes of operation and closure, where the biotic, abiotic and socioeconomic components are monitored, sampled, characterized and observed. With this information, an Environmental Management Plan (EMP) was designed with their respective programs in order to minimize, mitigate and prevent improperly carried out actions. The results, according to the noise monitoring exceeded the permissible limits established in the TULSMA and in the WHO, because it was obtained at night 82,44 dB and its limit is 55 dB, coming from the process of fatigue and vehicular noise. As for the characterization of the water taken as reference, the parameters: total nitrogen 28,23mg/l, fat oils 0,5mg/l, total coliforms 210 000 NPM/100ml and fecal coliforms 3060 NPM/100ml exceeded the permissible limits established in the TULSMA and the WHO, being considered a negative impact of critical importance. As for the soil, there is no impact on the resource, since it is encemented, however, the generation of organic waste produced in the processes of unloading and slaughtering are not well managed, due to the fact that all of these are mixed and have no previous treatment in the plant, generating negative impacts and of severe importance. At the end of this work, it is concluded that the "Frank" poultry processing plant does not have the necessary mechanisms to minimize noise levels, nor does it have a wastewater treatment plant; therefore, these black waters that come out of the slaughtering and cleaning process are not subjected to any basic treatment, nor does it have an instruction manual to classify solid and liquid waste, they are simply mixed and discarded in a temporary deposit. It should be noted that the presence of the plant generates a dynamism in the economy because it provides work to 40 families improving living conditions. Key words: Environmental impacts, environmental impact assessment, Environmental Management Plan.